The Comparison of Ketamine, Xylazine and Ketamine-Xylazine Combination to Rat (Rattus Norvegicus) - Ratna Widyawati; Bayu Dirgantara Syahputra Ayomi (VITEK : Bidang Kedokteran Hewan, 2015)
The mean of this research is to observed the OOA (Onset Of Action), DOA (Duration Of Action), Cardiovascular (CRT), respiration system (respiration type and respiration rate) on giving of Ketamine, Xylazine that compare to the combination of Ketamine-Xylazine to rat and reach the anesthetic choice that can fulfill the basic anestesia criteria ( sedation, analgesia, relaxation, safe and applicable).This research use 30 rats that separated in to 3 groups, each group consist of 10 rats. Group P1 got pre-anestesia treatment with atropine (0,05 mg/kg body weight) subcutaneously and 10 minutes latter is given the induction of anestesia with Ketamine (50-200mg/kg body weight) intramuscularly, Group P2 got pre-anestesia treatment with atropine (0,05 mg/kg body weight) subcutaneously and 10 minutes latter is given the induction of anestesia with Xylazine (5-10 mg/kg body weight) intramuscularly and Group P3 got pre-anestesia treatment with atropine (0,05 mg/kg body weight) subcutaneously and 10 minutes latter is given induction of anestesia with Ketamine and Xylazine intramuscularly.Result of the research to OOA and DOA (F < 0,05 < 0,01) show that faint time is earlier in the post injection of ketamine-xylazine. The result of research of anestesia duration to cardiovascular system (CRT) show that there is not real different for the three treatment (F > 0,05 > 0,01) while in the three treatment there is real different for the anestesia stage (F < 0,05 < 0,01). Result of the research for the anestesia duration in the respiration system especially in respiration type show that there is not real different in that three treatment (F > 0,05 > 0,01) while in the anestesia stage show that there is real different (F < 0,05 < 0,01). Research result about the respiration rate in the three treatment show that there is no real different (F > 0,05 > 0,01) so was the treatment in anestesia stage show that there is real different (F < 0,05 < 0,01).